SYSTEMATIC LITERATURE REVIEW ON TECHNOLOGICAL TURBULENCE IN MSMEs - Sugangga, Rayyan; IRADAH RAHMAN (Akademika : Jurnal Manajemen, Akuntansi, dan Bisnis., 2025)
Abstract. Technological turbulence is an important factor affecting the innovation performance of small companies in today's rapidly changing business environment. Technological turbulence refers to unpredictable technological changes that can have a significant impact on a business, especially in the context of innovation performance. Articles are compiled using Systematic Literature Review from the Scopus database for publishing searches from 1984 to 2024. The results of this study show that importance of adaptability, innovation and strategic orientation in managing the challenges posed by technological turbulence in various organizational contexts. In addition, future research could use longitudinal methods and need to carry out specific sectoral analyzes to understand how various industries are impacted by technological turbulence.